2021
DOI: 10.33258/birle.v4i1.1571
|View full text |Cite
|
Sign up to set email alerts
|

Development of Reading Materials with Coastal Culture Tapanuli Central for School Literation Movement in Basic School Pandan District

Abstract: The purpose of this study was to determine: (1) The results of the design of reading materials with coastal culture for literacy sources, (2) The results of expert validation on the design of reading materials containing coastal culture for literacy sources, and ( 3) The results of testing of reading materials with coastal culture. for literacy sources in Class V Elementary School, Pandan, Tapanuli Tengah. This type of research is the type of research development or Research & Development. The development … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
1
2
0
Order By: Relevance
“…This finding aligns with prior research, which has consistently shown that reading materials incorporating local culture is not only effective (Tarigan et al, 2019) but also beneficial for students (Aminullah et al, 2019). Such materials have been recognized for sparking student interest in reading (Nambiar et al, 2020) and fostering reading habits (Hamdani et al, 2021). The teacher's assessment and student feedback collectively confirm that the reading materials meet educational needs and are practical for use in English classrooms.…”
Section: 88 Strongly Agreesupporting
confidence: 86%
See 1 more Smart Citation
“…This finding aligns with prior research, which has consistently shown that reading materials incorporating local culture is not only effective (Tarigan et al, 2019) but also beneficial for students (Aminullah et al, 2019). Such materials have been recognized for sparking student interest in reading (Nambiar et al, 2020) and fostering reading habits (Hamdani et al, 2021). The teacher's assessment and student feedback collectively confirm that the reading materials meet educational needs and are practical for use in English classrooms.…”
Section: 88 Strongly Agreesupporting
confidence: 86%
“…For instance, Tarigan et al (2019) demonstrated the effectiveness of reading materials incorporating Karo culture in the school literacy movement for senior high school students. Similarly, Hamdani et al (2021) found that reading materials featuring Tapanuli culture supported students' reading habits. Oktarina et al (2022) revealed that developing recount text reading materials related to tourist attractions heightened student interest in learning and promoting their local areas in English.…”
Section: Introductionmentioning
confidence: 92%
“…The materials studied by students are information or facts, concepts, principles, In the interaction of learning activities in the classroom, both teachers and students have an equally important role (Hamdani, Sriadhi, & Eviyanti, 2021). The difference lies in the function and role of each.…”
Section: Introductionmentioning
confidence: 99%